Behavioural interactions between the lizard Takydromus tachydromoides and the praying mantis Tenodera aridifolia suggest reciprocal predation between them - Fukudome, Miyuki (J Ethol, 2016)
The Japanese lacertid lizard Takydromus tachydromoides and the praying mantis Tenodera aridifolia are sympatric generalist predators feeding on similar prey. To confirm reciprocal predation between them, we observed the behavioural interactions between the lizards and the mantises of different sizes in a laboratory condition. The lizards caught small mantises (from first to fifth instars), but sometimes escaped from large mantises (from sixth instar to adult). Large mantises occasionally showed catch responses to the lizards. The lizards sometimes caught the mantis without a tongue-flick response (sampling of chemical cues), and they sometimes did not catch the small mantises showing immobile or cryptic responses that prevent visual detection. These results suggested the primary role of vision on recognition of the mantis as a prey. The lizards spent a longer time to approach larger mantises. The time from orienting to catch was longer when the lizards showed tongue-flick responses. The lizard also spent a longer time before deciding to escape from the mantis than to catch it. Biological significance of these differences in timing was discussed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10164-016-0468-6) contains supplementary material, which is available to authorized users.